Estetika Seni Lukis Kaligrafi Karya Syaiful Adnan - Auliya, Aghni Ghofarun; Shokiyah, Nunuk Nur (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2013)
This research is a descriptive qualitative research. The object under study is the aesthetic value of the art of calligraphy Saiful Adnan. The author uses the techniques of data collection through literature review, observation, and interviews. The validity of the data using triangulation of data by utilizing the data sources and review interviews that have been conducted.Analysis of the data used are data reduction, data presentation, inference, and interpretation of data. To explain the aesthetics of painting calligraphy Saiful Adnan using interpretation approach Susanne K. Langer's aesthetic theory. The results of the study explained that, the character of the Arabic calligraphy art kaligarfi Adnan Saiful different from raw calligraphy character has evolved over the years. The character is known as khatkaligarfiSyaifuly. Calligraphy character formation through several internal and external factors. Internal factors include environmental factors Adnan Saiful place of origin, education factors, and spiritual factors. The external factors include factors phenomena that occur in the community and form factors of artistic calligraphy. The process has led to the formation of the character of the aesthetic value of the art of calligraphy Saiful Adnan symbolic color, shape, composition, and verses from the Qur'an with the meaning of the beauty of Islamic values in each painting calligraphySaiful Adnan.Â Keywords: Aesthetics, painting calligraphy, Saiful Adnan, Syaifuly.